SYMBOLS IN TEACHER’S WRITTEN FEEDBACK AND THEIR MEANINGS (RETAIN, 2014)
SYMBOLS IN TEACHER’S WRITTEN FEEDBACK AND THEIR MEANINGS Ida Apriyanti English Education, Languages and Arts Faculty, State University of Surabaya idaapriyanti26@gmail.com Ahmad Munir English Department, Languages and Arts Faculty, State University of Surabaya munstkip@yahoo.com Abstrak Balikan tertulis dari guru merupakan hal yang penting dalam proses belajar mengajar bahasa. Pendapat mengenai efek dari pemebrian balikan tertulis pada pekerjaan siswa menjadi topik yang banyak dibahas oleh para ahli, telah banyak penetian yang dilakukan terkait dengan topik ini. Sebuah penelitian yang dilaksanakan oleh Rahmawati (2013) menunjukkan bahwa pemberian balikan tertulis dapat menimbulkan kesalahan dalam mengartikan balikan tertulis dalam bentuk simbol. Maka dari itu penelitian ini bertujuan untuk mencari faktor-faktor yang memungkinkan menjadi penyebab salah pengartian atau perbedaan pengartian balikan tertulis dalam bentuk simbol. Penelitian inti merupakan sebuah penelitian deskriptif kualitatif, dengan melibatkan siswa kelas VIII-E di SMPN 2 Kunjang, Kediri and guru bahasa inggris kelas tersebut sebagai partisipan. Penelitian ini menggunakan tiga intrumen penelitian termasuk: dokumentasi, observasi dalam bentuk field notes dan wawancara. Hasil penelitian menunjukan bahwa guru menggunakan tiga jenis balikan tertulis yang berupa simbol antara lain: garis, inisial, dan kata. Meskipun kebanyakan dari simbol-simbol ini berhasil diartikan dengan pengertian yang sama oleh guru dan siswa, namun tetap ada perbedaan pengartian untuk beberapa simbol. Ada tiga factor yang memungkinkan memicu perbedaan pendapat terhadap simbol yaitu: ketidak jelasan arti simbol, ketidak jelasan penulisan simbol, dan ketidak konsistenan dalam memberikan balikan simbol sesuai dengan jenis kesalahan. Kata kunci: Balikan Tertulis, Simbol, dan Perbedaan Makna Abstract Written feedback is a crucial thing in language learning. The argument over the effect of giving written feedback to the students’ performance became an issue among the experts, numerous research had been done to investigate this issue. A result of study done by Rahmawati (2013), showed that the giving of written feedback might lead into students’ misinterpretation toward the written feedback in form of symbols. Thus, this study was aimed to seek the possible factors that lead into misinterpretation, or different interpretations toward written feedback in the form of symbols. This was a descriptive qualitative study, with the students of VIII-E of SMPN 2 Kunjang, Kediri and the teacher as the participants. This study used three instruments to collect the data including: documentation, observation field notes, and interview. It was found that the teacher used three forms of symbols while giving written feedback, namely: lines, initials, and words. Even though in interpreting these symbols the teacher and the students mostly had in the same point of view but, but it was found that sometimes they had different interpretation toward certain symbols. It was found that at least there were three possible factors that triggered the presence of different interpretation between the teacher and the students, including; the unclear meaning of symbols, the unclear drawing of symbols, and the inconsistency in giving symbols feedback based on the type of errors. Key Words: Written Feedback, Symbols, and Different Interpretation INTRODUCTION The attempts to improve students’ writing have been developed by the education practitioners for a long time. One of the strategies to improve student writing performance is by giving feedbacks to the students. The aim of giving feedback is to give the students any kinds of comments which are used to give such valuable guidance, directions or even hints in doing revision in their writing. Keh (1990) defines feedbacks on writing as an input from a reader to a writer with the effect of providing information to the writer for revision. Feedback helps the students and the teacher to match what is still in problem during the teaching learning section. Williams(2003) claims that written feedback is an essential aspect of English language writing activity . The giving of feedback will catch the students’ attention to their performance because of their eagerness to perform better by doing revision in it. This is in line with Hyland and Hyland (2006) who also claim that feedback is commonly seen as crucial for both encouraging and consolidating learning. Hence, the providing of feedback in the students writing will encourage the students to revise the errors and finally have a better writing. The way teachers give feedback to the students work will depend on the type of written work and the respond that is wanted. A basic distinction is needed to make in the teacher feedback, according to Ellis (2009) there are several types of teacher written feedback, including: direct feedback, indirect feedback, metalingusitic feedback, focus feedback, unfocused feedback, electronic feedback and reformulation feedback. Even though feedbacks may provide a good effect to the student’s writing production, the latest issues of giving feedback also reveal another view which found that the activity of giving feedback was a harmful thing to do. An argument coming from Truscott (1996) who claims that giving feedback is both ineffective and harmful and therefore it should be abandoned. Gray (2004) also argued that the use of grammar corrective feedback may be not effective in writing class because it may be harmful, it treats only the surface appearance of grammar and not with the way language development. Hyland (2003) argues that written feedback provided by the teacher is frequently misunderstood, sometimes being too vague prescriptions and inconsistent. There is a possibility that the students having a different interpretation to the feedback given by the teacher and it will be getting worse when there is no attempt between the students and the teacher to have the same interpretation over the feedback. The teacher also has a possibility of wrongly giving feedback to the students unconsciously the teacher might provide vague prescriptions so the feedback will be uneasy to be understood or sometimes the giving of feedback being inconsistent from one student to another student. A result of study done by Rahmawati (2013), dealing with the contra productive effects that teacher’s written feedback has toward the students’ tendency to rewrite error in their revision after the giving of feedback, showed that the giving of written feedback might lead into students’ misinterpretation toward the symbols, thus they rewrote errors in their revision. Symbols are a common tool used by teachers in providing feedback to the students’ work. Symbols as feedback is a kind of codes which are used to indicate that his or her use of target language is incorrect (Lightbown & Spada, 1999). Oshima and Hogue (1997) explain that correction symbols refers to the indication of types and locations of students error, it is normally done by underlining, circling, crossing out or any other kinds of symbols to help students focusing their attention to the error types. Symbols as feedback are signs that represent errors, by using symbols the teacher tells the student about the errors they made and direct the students doing revision. There are no fix symbols that should be used by the teacher. The symbols in Table 1 below were suggested by Harmer (2007) that are often used by the teachers to give feedback on the students writing. Table 1 The Symbols in Written Feedback Suggested by Harmer (2007) Symbol Meaning Incorrect Correct P Punctuation I bought (P) clothes, shoes and some trousers. I bought clothes, shoes, and some trousers. l Something has been left He told (l) that he was sorry He told me that he was sorry. WO Wrong order I caught a very fish big. (WO) I caught a very big fish. To avoid such different interpretation toward feedback symbols, according to Weigle’s (2001) suggestions, the teacher and the students should agree first of having certain symbols in written form and the way to interpret them. Thus even though the teacher must not use any certain symbols to give written feedback to the students’ work, still there should be an agreement on the limitation of symbols that are going to used among the teacher and the students and their meanings so that it can ease the students doing revision. The right interpretation of symbols will help the students to perform better in their revised writing but the problem may exist if the symbols are not interpreted in the right way, as the result of Rahmawati’s (2013) study that has been delivered in the previous paragraph. As no studies have explored the problem dealing with the cause of misinterpretation or in this study the researcher defines it as a phenomenon of different interpretation toward symbols as feedback, thus it is important to seek the further information dealing with this issue. By describing the meaning of symbols in the written feedback based on the teacher’s and the students’ view, therefore there could be noticed the possible factors that triggered different interpretation of symbols among them. This study was intended to answer the following questions: What symbols does the teacher use in giving feedback? What do all these symbols mean according to the teacher and the students? What make students have different interpretation on the meaning of symbols in the teacher’s written feedback? RESEARCH METHODS The students of VIII- E SMPN 2 Kunjang and the English teacher of this class were chosen as the participants of this study. This class consisted of 18 male students and 18 female students. The students did the writing activity, they wrote a paragraph of recount. Their works then were given feedback in the written form by the teacher. The writings that were given feedback by the teacher then would be returned to the students to be revised. Trough the result of the students’ revisions to the errors that had been given such a written feedback, the researcher analyzed the possible factors triggering the different interpretation toward symbols in the written feedback. In order to answer the research questions that had been mentioned before, the researcher collected the data trough three instruments, including: documentation, observation, and interview. The documentations in this study were gathered from students’ written work. The students’ written work aided the researcher to collect data about the number of symbols used by the teacher and to help the researcher making analysis to the meaning of symbols according to the students and find the causes of different interpretations to the meaning of symbols in the teacher’s written feedback between the students and the teachers. The observation was conducted in a nonparticipant observation, it was used to record the classroom activity during the implementation of teacher feedback and was used to record all important things that already seen, heard, and happened. The observation was in the form of unstructured field notes. An observation field note was used to aid the researcher during the observation in collecting the data about the teaching and learning process in the classroom, this field notes focused on the activities of the teacher and the students while asking and giving explanation of feedback especially in the form of symbols. This data was important to avoid the unwanted bias that may exist in the result of interview and to determine the objectivity of the result of the present study. The researcher interviewed both teacher and the students. The interview helped the researcher to seek the information of teacher’s and the students’ interpretation of symbols. Generally, these interview questions were focused on the meaning of various symbols in written feedback. Firstly, the documentations of students’ writings were tabled into two. The first table was used to mention all of the feedbacks which ware in the form of symbols and then they would be grouped into their category, then these symbols were given meaning based on the result of interview, researcher’s analysis of students writing, and the facts in the class. In the second table, the researcher used the data from students writing to write the students’ errors in their first essay and the revisions in their revised essay. It gave an opportunity for the researcher to make a possible meaning of symbols according to the students’ result of writing and its revision. Secondly, analyze the result of interview. The interviews which were conducted to the students were transcribed then were qualitatively analyzed to get the data of the students’ interpretation of symbols given by the teacher in their works, and the interview with the teacher was analyzed to seek the information of the teacher’s interpretation of symbols in her written feedback. Then, analysis of the result of the interviews with the researcher would show if there was a different interpretation of symbols between the teacher and students. The last, the observation field notes were analyzed according to the fact and the researcher interpretation. The researcher’s analysis was naturally based on the phenomena during the activity of giving teacher’s written feedback in the class. The analysis was used to strengthen the result of data gained from the table and the interviews, these data were important to avoid the unwanted bias that may exist in the result of interview. This was used to seek the factors triggering different interpretation of symbols between the teacher and the students. RESULTS AND DISCUSSION From the analysis of students writing, it was found that when giving written feedback the teacher used at least three forms of symbols as the written feedback, including: lines, initials, and words. The symbols which were in the form of lines, consisted of: circles, crosses, strikethroughs, arrows, bent arrows, double bent arrows, brackets and underlines (for the drawing of symbols see Table 1). The teacher also used initials to symbolize the errors made by the students, they were: “V1”, “V2”, “V3”, “be”, “be2”, “Obj”. Last, the feedbacks which were in the form of words were: subject, object, and milik (possessive pronoun). The teacher also combined, at least, two symbols to represent one idea such as: “(V2)” or “_______be2 ”. The table 1 showed the symbols used by the teacher. The symbols which were in the form of lines, according to Ellis (2009), it can be included into the indirect feedback because these lines were a kind of mark to sign the errors made by the students in their writing that were aimed to give the students a hint to do revision, these kind of symbols did not provide such a direct correction given by the teacher. The feedbacks which were in the form of initial can be included into metalinguistic feedback, Ellis (2009) confirms that metalinguistic feedback can be in the form of abbreviation or initial of labels for different kinds of errors, these labels of errors signing the students to the type of errors they made in their writing, it was aided the student doing revision based on the feedback symbols they received, while the feedbacks which were in form of words did not become a feedback which were suggested by any experts, because rather than used the full labels of error, most of the teacher prefers using initials or abbreviations as the label of errors. The meaning of symbols according to the teacher’s and the students’ view had the result of interview with the teacher and the result of researcher’s analysis of students’ writing as its sources of the data. By making use the information directly provided by the teacher through the interview and the analysis of the students’ writing, it can be summarized that the teacher gave such a classification for each errors. The teacher gave symbols as a feedback based on the type of errors made by the students and each of these symbols explicitly provided the information for doing revision. Because of there were a number of error types that made by the students, thus there were a number of symbols used by the teacher. In the Table 2 the researcher provided the explanation to the meaning of each symbol according to the teacher. Table 2 The Symbol Meanings According to the Teacher Second, the meaning of symbols according to the students’ view. The students’ revision of their writing gave the researcher such information of their interpretation toward the feedback given by the teacher the result also supported by the interviews with the students. For example, according to the S22’s (Student number 22) first writing (see Figure 1) and its revision (see Figure 2), it can be concluded that she interpreted the circled and the underlined words which were added by the “V2” symbol were the errors that need to be changed into the past participle, they were: look which was changed into looked, get into got, laugh into laughed, and go into went. In accordance with the result of the interview, she did revision to the words that were given double bent arrows symbol by changing the word order, such as experience ashamed which revised into ashamed experience and pants wet revised into wet pants. The following figures were the writings of S22. Figure 1 The S22’s First Writing Figure 2 The S22’s Revision Another analysis coming from S5’s writing (see Figure 3 and 4). From his writing, there could be seen that the S5 did revision to his writing. He got a feedback of “be2” that was given by the teacher, he interpreted it as “bez” thus he directly wrote “bez” in his revision. He had a different interpretation toward this symbol and it was probably caused by the unclear hand writing of the teacher. In the end, his revision gone wrong. Figure 3 The S5’S First Writing Figure 4 The S5’S Revision To ease in comparing the result of the teacher’ and the students’ interpretation of feedback thus, the reseacher made Table 3 below as the media to provide the meaning of symbols acccording to the students. Table 3 The Symbol Meanings According to the Students Generally the teacher’s and the students’ interpretation of symbols were the same, because the symbols used by the teacher were the symbols that quite easy to be understood. But by comparing the Table 2 and the Table 3 and also by looking at the students’ writing, they showed that there were some rewritten errors made by the students in their revision which were caused by the different interpretation over feedback symbols between the students and the teacher. The findings which were related to the meaning of symbols, according the views both teacher and the students, there was found that the teacher definitely had certain meaning for each symbol and obviously the students should follow it in order to revise the errors correctly, thus the meaning of the symbols would be match one another. Following Weigle’s (2001) suggestions, the teacher and the students should agree first to have certain symbols in written form and the way to interpret them, if there is no agreement dealing with the meaning of symbols in the feedback then it makes the meaning of symbols is unclear therefore it leads into misinterpretation of symbols but in contrast to Weigle’s (2001) suggestion, it was found that in the beginning of the lesson the teacher and students having no agreement dealing with the symbols that would be used and the teacher did not brief the students to understand the meaning of symbol in detail. Therefore, it made the students sometimes interpreted the symbols themselves, because not all of the students directly asked about the meaning of the symbols they had got to the teacher, thus the students made their own meaning of symbols. By making analysis to the data coming from the observation (field notes), documentation (students’ written work), and interview, it was found that there were at least three conditions leading to different interpretation toward symbols that happened between the teacher and the students, including: First, unclear meaning of symbols, because there was no fixed agreement dealing with the meaning of symbols they were going to use. Circles and underlines were the symbols that commonly used by the teacher, but the observation in the class showed that the teacher did not explain the meaning of these symbols in the beginning of the lesson. These symbols were frequently asked by the students if they were not added by any other comments and the students’ work showed that the students frequently revised the errors incorrectly for these symbols. Figure 5 The S4’s First Writing The Figure 5 showed that the teacher used some symbols to give feedback. The underlines were not added by any further comment thus the students feeling confused then revised the errors incorrectly. Because there was no agreement dealing with the meaning of symbols, then the students had an opportunity to interpret the symbols based on their own interpretation and it might become one of the factors made students had different interpretation of feedback symbols and finally did revision incorrectly. The second possible factor was the unclear drawing of symbols, the hand writing of the teacher sometimes seemed unclear. Figure 6 below was the S5’s first writing. It can be seen that the teacher circled is then added was the feedback symbol in the form of initial, “be2”. It seemed that S5 misinterpreted the symbol of “be2” because in his revision, he wrote “bez” instead of the form of is in the past tense, he thought that “be2” was “bez”. Figure 6 The S5’s First Writing The Figure 6 above showed the hand drawing of feedback symbols made by the teacher, the teacher drew “be2” (see Figure 6) unclearly, so it seemed like “bez”, thus the S5 interpreted this symbol as “bez”. This condition might lead the students to misinterpret the symbols, because the students might get confused because the drawing of symbols seemed too complex and unclear. The last possible factor was the inconsistency in giving symbol as written feedback. Being inconsistent in giving symbols as feedback to the students writing also became a factor that triggered the different interpretation toward symbols between the teacher and the students. The students might get confused because the teacher gave a different symbol for the same kind of mistakes. There were no fix symbols that should be used by the teacher, thus the teacher sometimes made arbitrary symbols while giving written feedback. This last result of the study strengthened the opinion coming from Hyland (2003) who argues that much written feedback is frequently misunderstood, sometimes being too vague prescriptions and inconsistent thus the symbols in the written feedback could lead the students had different interpretation from the expectation and make the students doing rewritten errors in their revised writing. CONLUSSIONS The research showed that the teacher used various kinds of feedback one of them was symbols. From the data gathered through the students’ writing then it could be seen that the teacher used a number of symbols to mark errors made by the students. They were in the form of lines, initials, and words. Generally the teacher’s and the students’ interpretation of symbols were the same, because the symbols used by the teacher were the symbols that quite easy to be understood. The possible factors leaded into different interpretation of symbols including: unclear meaning of feedback, unclear drawing of feedback, and the inconsistency while giving feedback symbol. REFERENCES Ellis, R. (2009). A Typology of Written Corrective Feedback Types. ELT Journal, 63(2). doi: 10.1093/elt/ccn023 Gray, R. (2004). Grammar correction in ESL/EFL writing classes may not be effective. 5. Retrieved from http://iteslj.org/Technique/Gray-WritingCorrection.html Harmer, J. (2007). How to Teach English. England: Pearson. Hyland, K. (2003). Second Language Writing. Cambridge: Cambridge University Press. Hyland, K., & Hyland, F. (2006). Feedback on Second Language Students' Writing: Contexts and Issues Applied Linguistics Series. Cambridge: Cambridge University Press. Keh, C. L. (1990). Feedback in the Writing Process: A Model and Methods for Implementation. ELT Journal, 44. Lightbown, P. M., & Spada, N. (1999). How Language are Learned. Oxford: Oxford University Press. Oshima, A., & Hogue, A. (1997). Introduction to Academic Writing. Addison Wesley: Longman. Rahmawati, E. (2013). Teacher's Written Corrective Feedback and Its Effect on The Students' Rewriting Erros in Writing Products. Post Graduate, State University of Surabaya, Surabaya. Truscott, J. (1996). The case against grammar correction in L2 writing classes. Language Learning, 46(2), 327-369. doi: 10.1111/j.1467-1770.1996.tb01238.x Weigle, S. C. (2001). Assessing writing. Cambridge: Cambridge University Press. Williams, J. G. (2003). Providing Feedback on ESL Students' Written Assignment. The Internet TESL Journal, 9(10).